Complications of intramedullary nailing—Evolution of treatment. (June 2017) - Wähnert, Dirk; Gehweiler, Dominic
Abstract: Intramedullary nailing of diaphyseal long bone fractures is a standard procedure in today's trauma and orthopedic surgery due to the numerous advantages (e.g. minimal invasive, limited soft tissue damage, load stability). In the last decade indications have been extended to the metaphyseal region. This was associated with problems and complications due to the reduced bone-implant interface. The changed anatomical conditions lead to decreased implant anchorage. Newly developed locking solutions overcome most of these problems. First, the number and also the orientation of the locking screws were adapted to allow a multiplanar locking. This results in increased implant anchorage in the soft metaphyseal bone, thus construct stability significantly improved. Additional options like angular stable locking have been introduced and furthermore enhanced construct stability especially in poor bone stock. As a perspective locking screw augmentation shows promising results in first biomechanical testing.